Size-dependent catalytic and antibacterial effects of phytogenically synthesized silver nanoparticles (Kuwait Journal of Science)
This study describes an eco-friendly phytosynthesis method to produce two different-sized silver nanoparticles utilizing aqueous extracts derived from Desmodium styracifolium (Osbeck) Merr. (Fabaceae) (DS-AgNPs) and Helicteres hirsuta Lour. (Malvaceae) (HH-AgNPs). The optimization process including the four main parameters of extract-to-silver volume ratio, silver ion concentrations, reaction time, and reaction temperature, was carried out using Taguchi method. The characterization of the phyto-synthesized AgNPs involved UV–Vis, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared (FTIR) spectroscopy, and energy-dispersive X-ray spectroscopy (EDX) analysis. A novel aspect of this study is the comparison of the catalytic and antibacterial activities of AgNPs with different sizes using extracts from two separate plant sources. The catalytic efficacy of AgNPs was investigated in the reduction reaction of methylene blue and bromocresol green using a sodium borohydride solution as a reducing agent. The antimicrobial assay demonstrated inhibitory effects against a range of bacterial strains including Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Salmonella enterica. The research findings confirm that size plays a vital role, as DS-AgNPs with an average diameter of 22 nm show a higher efficiency of catalytic and antibacterial activity compared to HH-AgNPs with an average diameter of 43 nm. © 2025 The Authors